Sistem Informasi Penilaian Mandiri Untuk Tata Kelola Teknologi Informasi Pada PT Petrokimia Gresik (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
The assessment of information technology governance is a crucial aspect of managing IT resources to align the implementation of information technology with business operations and corporate objectives. At PT Petrokimia Gresik, IT governance assessment is still carried out using conventional methods. Therefore, this research aims to design and develop a Self-Assessment Information Technology Governance System at PT Petrokimia Gresik. This research begins with user interviews and a literature review from various sources such as journals, reference documents, and COBIT 2019 books. The system development is conducted using the SCRUM method to produce a system that meets user requirements. In the SCRUM method, there are four main activities: sprint planning, daily scrum, sprint review, and sprint retrospective. This information system was successfully developed using the Laravel framework, which proved to streamline web application development. The implication of this research is the creation of a Self-Assessment Information Technology Governance System. Based on the results of user acceptance testing, the system produced has been well-received and meets user needs.